PENERAPAN TEKNIK ROLE PLAYING UNTUK MENINGKATKAN SELF CONFIDENCE SISWA KELAS X E SMA NEGERI 5 BANJARMASIN - Wiyono Wiyono (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
Self Self Confident is an important factor that can affect the life of a successful person, a person who self confidence low in students including dared not ask questions or concerns during the learning process, feel the physical form is not perfect of friends to another, do not dare to appear in front of the class, talking nervously if the front of the crowd, low socioeconomic status, and have friends who are limited so that the impact on their social interactions, eg impact in their social interactions decreased academic achievement, insecure, often aloof and reserved. Based on the above problems, the researchers are interested in doing research, entitled Implementation Techniques for Increasing Self Confidence Roleplaying 10th E Grade Students Of Senior High School 5 Banjarmasin. This type of research is quantitative research with experimental research design. This place in Senior High School 5 Banjarmasin whose population the 10th E grade students numbering 34 students. Sampling technique used in this study is a sampling technique is purposive sampling with the number of 12 students.Data were analyzed using t test and demonstrate thit 51.83> ttab2,228 with a 95% confidence level. Thus showing that the